A Text Mining Approach to Analyzing the Role of Negative Sentiment Words in News Articles on Suicide and Related Incidents - Selamat Subagio; Samsir Samsir; Abdul Hakim Dalimunthe; Ronal Watrianthos (Bulletin of Information Technology (BIT), 2024)
This study examines the role of negative sentiment words in news media coverage of suicide and related incidents through analysis of 1,515 news articles published between 2019 and 2024. Using advanced text mining techniques and sentiment analysis, we investigated patterns in emotional language use and their impact on public discourse. The research revealed frequent usage of negative sentiment words such as "crisis" (256 occurrences), "despair" (214 occurrences), and "death" (189 occurrences), which significantly influenced the emotional framing of these sensitive topics. Statistical analysis showed strong correlations between negative sentiment words and mental health-related terms (correlation value 0.75), indicating consistent patterns in media narrative construction. Temporal analysis identified a notable increase in negative sentiment during the COVID-19 pandemic (2020-2021), followed by a shift toward more solution-focused coverage in 2022-2024. The findings suggest that while negative sentiment words are inherent in covering suicide-related topics, their use can be balanced with solution-oriented language to promote more responsible reporting. This research contributes to understanding how emotional language shapes public discourse on mental health crises and provides insights for developing more effective guidelines for responsible journalism.